Sex × Gender and Sexual Orientation in Relation to Stress Hormones and Allostatic Load. (8th July 2019) - Juster, Robert-Paul
In this selective review, emerging literature linking biological sex, sociocultural gender, and sexual orientation to stress hormone functioning and multisystemic physiological dysregulations are summarized. Beyond sex as a binary biological variable, continuums of sex hormones, gender roles, gender identity, and sexual orientation each uniquely help delineate pathways and mechanisms linked to stress-related disease trajectories. This implicates glucocorticoid functioning and allostatic load, the "wear and tear" of chronic stress in synergy with unhealthy behaviors. Clinical considerations are also discussed for the field of gender medicine.